2006
DOI: 10.1080/01421590600622723
|View full text |Cite
|
Sign up to set email alerts
|

BEME systematic review: Predictive values of measurements obtained in medical schools and future performance in medical practice

Abstract: There is a need for a more consistent and systematic approach to studies of the effectiveness of undergraduate assessment systems and tools and their predictive value. Although existing tools do appear to have low to moderate correlation with postgraduate training performance, little is known about their relationship to longer-term practice patterns and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
121
1
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(131 citation statements)
references
References 62 publications
3
121
1
6
Order By: Relevance
“…[2][3][4][5][6] However, the relationship between commonly available measures of academic performance and future competency is largely unknown. 2 Andriole et al found that medical school grades and USMLE exam scores predicted program director ratings of surgical interns. 7 Knowledge of which markers predict poor performance during internship would be useful to medical school admission committees, medical educators, and intern program directors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6] However, the relationship between commonly available measures of academic performance and future competency is largely unknown. 2 Andriole et al found that medical school grades and USMLE exam scores predicted program director ratings of surgical interns. 7 Knowledge of which markers predict poor performance during internship would be useful to medical school admission committees, medical educators, and intern program directors.…”
Section: Introductionmentioning
confidence: 99%
“…2 For example, standardized tests tend to predict future standardized test scores and grades earned at 1 educational level tend to predict grades earned at subsequent training levels. [2][3][4][5][6] However, the relationship between commonly available measures of academic performance and future competency is largely unknown. 2 Andriole et al found that medical school grades and USMLE exam scores predicted program director ratings of surgical interns.…”
Section: Introductionmentioning
confidence: 99%
“…But of the 9 published BEME reviews, only one was able to estimate an overall effect. Ironically, this was a review of predictive validity of assessment methods, based on correlational studies (Hamdy et al 2006). But no one would suggest that we abandon educational experiments although a few people (Regehr 2010;Mennin 2010), have suggested, or at least implied, just that.…”
mentioning
confidence: 99%
“…31 In summary, these findings highlight a potentially negative impact of breaking from the traditional curriculum. Our study is limited by several factors.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent BEME systematic review of predictive values of medical school performance and future performance, clerkship honors and grades correlated positively with supervisor rating during residency. 31 Similarly, Taylor et al reported that medical school GPA was the best predictor of residency directors' ratings of interns. 32 Others have found clerkship honors to predict performance on the American Board of Specialty Examination 33 along with residency performance.…”
Section: Discussionmentioning
confidence: 99%